Dosimetric Comparison of Conventional 3D-Conformal Radiotherapy (3DCRT) and Volumetric-Modulated Arc Therapy (VMAT) for Head and Neck Cancer - Thanvi, Shubhangi; Patidar, Yaman; Sharma, Neeti; Rawal, Trilok; Sinwer, Rajesh Kumar; Jakhar, Shankar Lal; Harsh, Kamlesh Kumar; Kumar, H S (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Advancements in radiation oncology have improved outcomes for patients with head and neck cancer, enabling dose escalation to tumors while minimizing exposure to surrounding healthy tissues. This study aimed to compare the dosimetric characteristics of radiotherapy treatment planning using 3DCRT and VMAT for head and neck cancer. Methods: This prospective study included 50 patients with head and neck cancer. Twenty-five patients were treated with 3DCRT, and 25 were treated with VMAT. Both treatment plans were evaluated to compare the dosimetric efficiency of VMAT and 3DCRT in terms of planning target volume (PTV) coverage, homogeneity index, conformity index, and doses to organs at risk (OARs). Results: The dose to 98% of the PTV (D98%) for PTV66 was 59.39 Gy for VMAT and 51.82 Gy for 3DCRT. The conformity index was 1.0816 for VMAT and 1.4472 for 3DCRT plans, with a statistically significant difference. The homogeneity index was 0.1473 for VMAT and 0.2997 for 3DCRT, indicating that VMAT plans were more homogeneous. OAR sparing was also better with VMAT compared to 3DCRT, particularly for OARs in close proximity to the target volume, such as the parotid glands, brainstem, and optic nerve. Conclusion: Compared to 3DCRT plans, VMAT plans demonstrated significantly better target coverage, homogeneity, and dose conformity. Doses to OARs, such as the spinal cord and parotid glands, were also reduced. Additionally, VMAT treatment delivery was more efficient.